Testicular Leydig Cell Tumor with Metachronous Lesions: Outcomes after Metastasis Resection and Cryoablation - Julio J. Geminiani; Stephen D. Marshall; Tammy S. Ho; Steven B. Brandes (Case Reports in Urology)
Leydig cell tumors represent 3% of testicular masses and usually occur in prepubertal boys and men between 30 and 60 years of age. Leydig cell tumors are benign in children but can be malignant in 10% of adults. This case report describes a 41-year-old patient who was diagnosed with a Leydig cell tumor that originated in his right testicle that subsequently metastasized to his liver, lungs, and retroperitoneum. We discuss the patient’s presentation and review the radiographic findings, surgical treatment, surgical pathology, chemotherapeutic treatment, and published literature on this rare pathology.